IMPLEMENTASI AATHP (ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTIO) DALAM PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN DI INDONESIA PERIODE 2014-2017 - Reza Kristian Juldri, - (2018)
This research entitled "Indonesia-ASEAN Cooperation on Dealing with Forest Fires in Indonesia in the AATHP Framework (ASEAN Agreement on Transboundary Haze Pollution) 2014-2017 Period". Cases of forest and land fires in Indonesia has been a common problem especially for Indonesia's neighbors, which has led into spreading to the ASEAN region. The case is handled jointly with ASEAN countries, that forest / land fires and cross-border smoke haze pollution has reached a very apprehensive condition. ASEAN as an umbrella organization in Southeast Asian countries has made an agreement that focuses on dealing with cases of forest / land fires and cross-border air pollution, known as the ASEAN Agreement on Transboundary Hazard Pollution (AATHP). Indonesia is the last country to ratify the agreement in 2013. The reason Indonesia ratified the agreement is because of the insistence of member countries that has first ratified and the agreement will be used by the author to answer questions from research conducted, the author uses several concepts and theory. The author uses the theory of International Organization to explain the process of formation of cooperation that produces AATHP. After that the authors use the concept of ASEAN and the concept of problem solving in ASEAN to clarify the cooperation of Indonesia with ASEAN through the existing settlement process in ASEAN. Then the author uses the AATHP concept itself, to explain the AATHP section and its implementation. The author also uses the green theory (Green Theory) to explain how important environmental cases to become one of the world's major concerns. The author also uses the qualitative method by explaining the case, as well as the collection of primary and secondary data through data analysist and interviews. The results of this study will explain the implementation that has been realized by AATHP since the ratification made by Indonesia